Pengaruh Jenis Hijauan Pakan dan Lama Penyimpanan Terhadap Sifat Fisik Wafer - Retnani, Yuli; Basymeleh, Suhail; Herawati, Lidy (Fakultas Peternakan Universitas Jambi, 2009)
The aim of this experiment was to evaluate the effect of different forage wafer variety, storage periods and the interaction on wafer physical characteristics. The experimental design used in this research was Factorial Completely Randomized Design with 2 factors and 4 replications. Factor A was forage variety composing wafer (R1 = 100% grass; R2 = 100 % maize straw; R3 = 100% maize steam, R4 = 50% field grass + maize straw; R5 = 50% field grass + maize steam; R6 = 50% maize straw + 50% maize steam. The variables were water content, water activity and density of wafer. Data collected was analyzed with ANOVA and Duncan Range Test would be used if the result was significantly different. The forage vaiety was very significant (P<0.01) on moisture content, water activity and density of wafer. The storage period was very significantly (P<0.01) increasing on water content, water activity and decreasing wafer density. There was very significant interaction (P>0.01) between forage variety and storage period on water content, water activity and density of wafer.